Anthropocene and Capitalocene: In Search of a Fusion of Horizons - Szaj, Patryk (Porównania, 2021)
The article joins the discussion between the Anthropocene and the Capitalocene. It begins with a reconstruction of the objections to the first one made by, among others, Jason W. Moore, Eileen Crist or Donna Haraway (incorrect diagnosis of the causes of the ecological and climate crisis, ignoring the unequal responsibility for this crisis, maintaining the anthropocentric vision of the world). Subsequently, the author presents counterarguments of the supporters of the Anthropocene, including Ian Angus, Clive Hamilton, and Dipesh Chakrabarty (the Anthropocene does not ignore the economic and political context, supporters of the Capitalocene make an unjustified transfer of geological diagnoses to the field of sociology, the narrative about capitalism is not a broad enough framework to study climate change). The end of the article attempts to fuse the horizons of both concepts. The author sees them as two versions of climate hermeneutics, attempting to understand what is happening to our world and to work out an answer to this process.